2016
DOI: 10.1002/jcla.21913
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Treponema pallidum Sp. Pallidum DNA in Cerebrospinal Fluid (CSF) by Two PCR Techniques

Abstract: Beyond some limitations of the study, which are discussed here, both PCR techniques seem to be useful for the diagnosis of neurosyphilis, although 47-PCR presents a higher sensitivity and polA-PCR a higher specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 32 publications
0
14
0
7
Order By: Relevance
“…A systematic review and meta-analysis concluded that T. pallidum PCR was more efficient for confirmation than to exclude syphilis diagnosis in lesions 129 . Recent research indicates that this technology may be helpful for the diagnosis of neurosyphilis by the detection of T. pallidum DNA in the cerebrospinal fluid (CSF) of patients with syphilis, particularly among HIV-infected individuals 130,131 .…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%
“…A systematic review and meta-analysis concluded that T. pallidum PCR was more efficient for confirmation than to exclude syphilis diagnosis in lesions 129 . Recent research indicates that this technology may be helpful for the diagnosis of neurosyphilis by the detection of T. pallidum DNA in the cerebrospinal fluid (CSF) of patients with syphilis, particularly among HIV-infected individuals 130,131 .…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%
“…In general, we recommend that all CSF samples be tested for VDRL even if the indication for the LP was not related. PCR testing for CSF infection is controversial, with 50% of neurosyphilis patients testing negative (Castro et al, 2016). Appropriate treatment of neurosyphilis should reduce the CSF pleocytosis and protein by 6 months after treatment, but CSF VDRL test results may remain reactive for at least 2 years.…”
Section: Neurosyphilismentioning
confidence: 99%
“…DNA extraction. T. pallidum DNA was isolated as previously described (19). Briefly, DNA was extracted from 200 µl of whole blood and DNAzol (Invitrogen; Thermo Fisher Scientific, Inc., Waltham, MA, USA) was used to extract DNA from specimens, according to the manufacturer's protocols.…”
Section: Methodsmentioning
confidence: 99%